Efektivitas Kerja Sama Pembangunan Internasional: Pencapaian Global dan Pengalaman Indonesia dalam Good Governance - Albert Triwibowo; JÃ¶rn Dosch (Andalas Institute of International Studies UNAND, 2025)
One of the important topics in international relations is international development cooperation, particularly good governance. Good governance has long been a crucial pillar of international development cooperation. However, there has been little discussion on the effectiveness of development cooperation in the area of good governance. This paper focuses on global achievements and Indonesiaâ€™s experiences in development cooperation, especially in good governance program. It argues that the most successful sector in the agenda of good governance globally is related to electoral assistance. Meanwhile, the decentralization, human rights and rule of law agendas have been shown to have positive, albeit limited, impacts. Here, Indonesia can be categorized not only as a recipient but also as a donor of aid. This allows Indonesia to play a role as a bridge between donor and recipient countries. This paper uses a qualitative methodology with a narrative approach and incorporates the concepts of international development cooperation, good governance and the role of new emerging donors.